The asthmatic athlete: Inhaled Beta-2 Agonists, sport performance, and doping - McKenzie, D. C.; Fitch, K. D. (Clinical Journal of Sport Medicine, 2011)
The asthmatic athlete has a long history in competitive sport in terms of success in performance and issues related to doping. Well documented are detailed objective tests used to evaluate the athlete with symptoms of asthma or airway hyperresponsiveness and the medical management. Initiated at the 2002 Salt Lake City Games, the International Olympic Committee's Independent Asthma Panel required testing to justify the use of inhaled beta-2 agonists (IBAs) in Olympic athletes and has provided valuable guidelines to the practicing physician. This program was educational and documented the variability in prevalence of asthma and/or airway hyperresponsiveness and IBA use between different sports and different countries. It provided a standard of care for the athlete with respiratory symptoms and led to the discovery that asthmatic Olympic athletes outperformed their peers at both Summer and Winter Olympic Games from 2002 to 2010. Changes to the World Anti-Doping Agency's Prohibited List in 2010 permitted the use of 2 IBA produced by the same pharmaceutical company. All others remain prohibited. However, there is no pharmacological difference between the permitted and prohibited IBAs. As a result of these changes, asthmatic athletes are being managed differently based on a World Anti-Doping Agency directive that has no foundation in pharmacological science or in clinical practice.